Laser cutting in Ti-6Al-4V sheet: DOE and evaluation of process parameters Informative - Andersson, Nils; Granberg, Carl (My University, 2015)
Different Titanium alloys are frequently used in the Aerospace industry owing to its attractive properties at high temperature service. Manufacturing of those parts are performed by different conventional and non-conventional methods where Laser Cutting are one of the latter. High demands on quality and security within the aerospace industry results in high requirements on the part after cutting. To accommodate the requirements it is necessary to possess knowledge about how the laser cutting process affects the material in terms surface finish and heat affected zone. Therefore, this thesis aims to investigate the effect of different laser cutting process parameters, namely material thickness, cutting speed, beam power, gas pressure and lens focal point and how a variation of their level affect the properties of a cut part. The alloy used for this study is Ti-6Al-4V, an alloy frequently used for manufacturing of engine parts in the aerospace industry. Experiments were planned via the statistical method Design of Experiment and two separate full factorial test plans were prepared. Samples were cut from different sheet thicknesses of the alloy Ti-6Al-4V according to the test plan. Sections from the samples were later on evaluated by measuring the heat affected zone, the surface irregularity and burr height. Additional hardness measurements not included in the test plan was also performed. The results showed that the material thickness and cutting speed were the parameters with strongest impact on the result. Also beam power and gas pressure showed an impact. Increased hardness in the heat affected zone was observed. Some measurements contained to much noise which led to that they could only serve as indicative and no conclusions could therefore be drawn from them.
Keywords: Materialvetenskap; Materialteknik; Materials Science; Materials Engineering